Utilization and Awareness of Unani Medicine among Adults in Delhi, India: A Survey-based Study - Khan, Asim Ali; Janardhanan, Rajiv; Kishore, Jugal; Saeed, Shazina; Das, B.C.; Parveen, Shagufta; Kesharwani, Prashant; Karwasra, Ritu; Sahebkar, Amirhossein; Selvamurthy, W. (Current Traditional Medicine, 2025)
ObjectivesThe objective of this study is to assess the level of knowledge, practice, and usage of Unani medicine among 250 participants in different areas of New Delhi, India.Materials and MethodsA cross-sectional, observational descriptive survey with a sample size of 250 people was carried out in New Delhi utilizing a pretested, predesigned, and structured questionnaire to evaluate the awareness and usage patterns of Unani medicine. The study was conducted at three different spots in different regions of New Delhi.ResultsWith a mean age of 40.056 ± 10.77 years and a range of 18 to 65 years, the 250 participants were divided into 66% men and 34% women. 60% of the population who had been adopted had knowledge of Unani medicine, and 54.6% of them relied on Unani medicine as a treatment regime. 40% of users reported Unani medicine due to lack of no or minimal side effects. Contrary to this, among non-user (n = 68), 51.4% populace considers Unani medicine as the slow onset of action medication. Although a small percentage of users (6.1%) chose to use Unani completely, most preferred it as an adjunct to allopathic care.ConclusionFindings in the survey-based study depict that the awareness of Unani medicines is better than the utilization pattern. There is an urge and opportunity to advance health education and change people's perceptions of the Unani medical system.
Keywords: Traditional medicine